ANALISA TINGKAT KERUSAKAN JALAN DAN PERENCANAAN LAPIS TAMBAHAN (OVERLAY) (Studi Kasus: Ruas Jalan Bangsing-Padangan, Kecamatan Pupuan, Kabupaten Tabanan) - Gede Sumarda; I Made Sudarma; I Kadek Darma Wirawan (Jurnal AKSES, 2021)
Bangsing-Padangan road is a road located in Pupuan District, Tabanan Regency. This road is a Class IIIC Local road type. Bangsing-Padang road is traversed by 4 villages. The damaged section is 2km. The most visible types of damage are cracks, large holes, sinking, and peeling. The damage is very disturbing to road users, therefore it is necessary to analyze the level of road damage and plan additional layers (Overlay). The PCI (Pavement Condition Index) method and the bina marga component analysis method were used in this study. From the analysis results, it was found that subsidence damage was more dominant than other types of damage, namely 57.44%, 35.27% cracked damage, and 38.29% hole damage. The results of the PCI (Pavement Condition Index) method obtained are 47.9% in moderate (Fair) conditions. From the results of the calculation of the bina marga component analysis method, the results obtained are D0 (Overlay) = 6.05cm using Laston material, D1 (Surface Layer) = 7cm using Lapen material, D2 (Upper Foundation Layer) = 15cm using stabilization material with lime, D3 (Foundation Layer) bottom) = 11cm using class A sirtu material.